Experience and Outcomes at a Specialized Clostridium difficile Clinical Practice - Tariq, Raseen (Mayo Clin Proc Innov Qual Outcomes, 2017)
OBJECTIVE: To report our experience with and outcomes among patients referred to a specialized Clostridium difficile clinical practice. PATIENTS AND METHODS: We retrospectively identified consecutive patients referred for Clostridium difficile infection (CDI) management from January 1, 2013, through May 30, 2015. Data were collected for demographic characteristics, CDI history, final diagnoses, and management. RESULTS: Overall, 211 patients (median age, 65 years; 66.4% women) were included. The most common indications for referral were recurrent CDI in 199 patients (94.3%), first CDI episode in 5 patients (2.4%), and chronic diarrhea in 7 patients (3.3%). After evaluation, the diagnoses were recurrent CDI in 127 patients (60.2%), resolved CDI in 36 patients (17.1%), first-episode CDI in 5 patients (2.4%), and non-CDI in 43 patients (20.4%). The most common non-CDI diagnoses were postinfection irritable bowel syndrome (PI-IBS) in 32 patients (15.2% overall), inflammatory bowel disease (n=3), small intestinal bacterial overgrowth (n=2), microscopic colitis (n=1), and asymptomatic C difficile colonization (n=2). Two patients had diabetic gastroparesis and food intolerances, and 1 had chronic constipation with overflow diarrhea. Of 127 patients with recurrent CDI, 30 (23.6%) received antibiotics; of these 30, 12 had antibiotic treatment failure and received fecal microbiota transplantation (FMT) for recurrent CDI. Among 97 patients (76.4%) who underwent FMT, 85 (87.6%) were cured after the first FMT, 5 were cured after the second FMT, and 7 were treated with antibiotics for FMT failure, with resolution of symptoms. CONCLUSION: A substantial proportion of patients referred for CDI subsequently received alternative diagnoses; PI-IBS was the most common. Patients being referred for recurrent CDI should be evaluated carefully for alternative diagnoses.